Planned Neck Dissection Following Radiation Treatment for Head and Neck Malignancy. (24th September 2012) - Dautremont, J. F.; Brake, M. K.; Thompson, G.; Trites, J.; Hart, R. D.; Taylor, S. M.
Abstract : Introduction . Optimal therapy for patients with metastatic neck disease remains controversial. Neck dissection following radiotherapy has traditionally been used to improve locoregional control. Methods . A retrospective review of 28 patients with node-positive head and neck malignancy treated with planned neck dissection following radiotherapy between January 2002 and December 2005 was performed to assess treatment outcomes. Results . Median interval to neck dissection was 9.6 weeks with a median number of 21 + 9 lymph nodes per specimen. Ten of 31 (32%) neck dissection specimens demonstrated evidence of residual carcinoma. Overall survival at two years was 85%; five-year overall survival was 65%. Concurrent chemotherapy did not impact the presence of residual neck disease. Conclusion . Based on the frequency of residual malignancy in the neck of patients treated with primary radiotherapy, a planned, postradiotherapy neck dissection should be strongly advocated for all patients with advanced-stage neck disease.